2015
DOI: 10.1093/occmed/kqu214
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced hearing loss and combined noise and vibration exposure

Abstract: This study confirms previous findings of greater hearing loss at higher frequencies in workers with VWF, but also found a significant difference in hearing loss at low frequencies. It therefore supports the association between combined noise and hand-arm vibration (HAV) exposure and NIHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 19 publications
1
52
0
3
Order By: Relevance
“…The older guinea pigs were two-fold more sensitive to vibration than younger animals [49]. The combination of noise and vibration during the use of hand-held vibrating tools increased the risk of hearing loss in industrial workers [6,52]. Increased oxidative stress and chronic inflammation are also associated with ageing [53], and age-related cochlear structural alterations and degeneration of sensory and neural cells also occurred [54] that resembles normal aging.…”
Section: Evidence For the Role Of Oxidative Stress In Hearing Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The older guinea pigs were two-fold more sensitive to vibration than younger animals [49]. The combination of noise and vibration during the use of hand-held vibrating tools increased the risk of hearing loss in industrial workers [6,52]. Increased oxidative stress and chronic inflammation are also associated with ageing [53], and age-related cochlear structural alterations and degeneration of sensory and neural cells also occurred [54] that resembles normal aging.…”
Section: Evidence For the Role Of Oxidative Stress In Hearing Disordersmentioning
confidence: 99%
“…In order to develop an effective preventive strategy, the major cellular defects that initiate and promote hearing loss should be identified. Several studies of the past decades indicate that increased oxidative stress [1][2][3][4][5][6], inflammation [7][8][9][10][11][12][13], and glutamate [14][15][16] play a central role in the initiation and progression of hearing defects. Therefore, reducing these biochemical defects simultaneously may be one of the rational strategies for the…”
mentioning
confidence: 99%
“…For example, a study of 199 Finnish forest workers found that aging was the main risk factor, followed by occupational noise exposure, and the presence of vibration in the work [20]. Furthermore, in the studies by Iki and Turcot greater hearing alterations were observed over time among forest workers who also suffered from white finger disease induced by hand and arm vibration [21,22]. In addition to causing communication difficulties, impairments related to hearing loss can in turn generate stress, anxiety, irritability, decreased self-esteem, social isolation, and loss of productivity, as well as impair the performance of activities of daily living, resulting in costs for the individual, family, company and society [23].…”
Section: Occupational Heat Exposure Assessment (A) Logging Industrymentioning
confidence: 99%
“…Besides noise, other well-established risk factors include vibration,4 smoking, organic solvent,5 long-term stress exposure and socioeconomic status 6. However, for workers exposed to a similar level of noise or other environmental factors, the extent of their hearing loss varies 7.…”
Section: Introductionmentioning
confidence: 99%